Evaluasi Penerapan Manajemen Waktu Dan Biaya Pada Proyek Pembagunan Puskesmas Jawakisa Kecamatan Aesesa Selatan Kabupaten Nagekeo - Meo, Yohanes; Gare, Mansuetus; Kota, Ireneus; Tan, Valentinus (TEKNOSIAR, 2024)
The construction of the Jawakisa Health Center is located in Tengatiba Village, South Aesesa District, Nagekeo Regency, in the implementation process did not meet the planned time, so the development project experienced delays. The purpose of this research is to evaluate the estimated costs and completion time for the construction of the project. This research uses quantitative methods by evaluated cost and time estimates for work that has been completed, and that has not been completed. The results of analysis using the value of results method are very effective in evaluating costs and time on the project. With the BCWS value for week 21 amounting to IDR 1,727,185,767.85, BCWP value for week 24 IDR 1,527,868,528.23, ACWP week 24 amounting to IDR 1,419,717,920.89, SV value – IDR 199,317.23, indicating the actual schedule is behind the planned schedule, CV value IDR 108,150.60, indicating the costs obtained is greater than the costs incurred, the SPI value for the 24th week is 0.88 indicating poor cost performance and wasteful compared to the planned schedule, the CPI value = 1.07 which means good and economical cost performance and shows the time needed for work that has not yet been completed. completed was 4.54 weeks while the total time to complete the entire project was 28.5 weeks and the estimated cost for the remaining work was Rp. 186,277,791.91 and the estimated total cost to complete all the work was Rp. early to optimize project results to the maximum.